2022
DOI: 10.1111/imj.15536
|View full text |Cite
|
Sign up to set email alerts
|

Low rates of venous thromboembolism in hospitalised COVID‐19 patients: an Australian experience

Abstract: Background Venous thromboembolic (VTE) complications appear common in hospitalised COVID‐19 patients, particularly among critically ill patients in intensive care units. However, there is significant heterogeneity in the reported use of thromboprophylaxis. Aims The primary objective was to determine rates of symptomatic VTE in hospitalised COVID‐19 patients. Secondary objectives were to assess adherence to an institutional risk‐adapted thromboprophylaxis guideline, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…3,17 There were two previous observational studies in Australia measuring the incidence of VTE and pulmonary embolism (PE) in hospitalised patients. In the first study of 86 patients in 2020, 18 there were no VTE events identified. In the second study of 65 patients in 2020, 10% of patients developed PE.…”
Section: Introductionmentioning
confidence: 99%
“…3,17 There were two previous observational studies in Australia measuring the incidence of VTE and pulmonary embolism (PE) in hospitalised patients. In the first study of 86 patients in 2020, 18 there were no VTE events identified. In the second study of 65 patients in 2020, 10% of patients developed PE.…”
Section: Introductionmentioning
confidence: 99%